The Evaluation of Organic Acids and Probiotic Cultures to Reduce Salmonella enteriditis Horizontal Transmission and Crop Infection in Broiler Chickens - Jarquin, R.L.; Nava, G.M.; Wolfenden, A.D.; Donoghue, A.M.; Hanning, I.; Higgins, S.E.; Hargis, B.M. (International Journal of Poultry Science, 2007)
An Organic Acid Mixture (OAM) was evaluated for efficacy against Salmonella enteritidis (SE) horizontal transmission and crop colonization in broiler chickens. The biocidal efficacy of the OAM (0.024% tannic, 0.042% lactic, 0.048% butyric and 0.048% acetic), was initially determined in vitro by treating a feed suspension inoculated with SE. The OAM was effective at reducing SE by at least 1 log unit in the feed suspension (P = 0.05). Treatment with the OAM was also assessed in combination with a probiotic treatment to evaluate effectiveness against horizontal transmission. One hundred newly hatched chicks were administered 3 treatments of OAM or probiotic, or 3 treatments of both OAM and probiotic over a 10 d period. Chicks (n = 20/group) were orally challenged with a 105 cfu mL-L culture of SE prior to treatment to act as sources for horizontal transmission. Ceca were collected and cultured for SE after 10 or 20 d. Horizontal transmission was reduced with OAM treatment solely (P = 0.05) or in combination with probiotic (P = 0.05). However, no apparent advantage to using both treatments was observed. The ability of the OAM to reduce SE crop contamination was determined by challenging market aged broilers with a 109 cfu mL-L culture of SE and administering the OAM in drinking water. Broilers were challenged with SE and immediately given the OAM or given the OAM 2 d prior to SE challenge. OAM was valuable in preventing horizontal transmission but did not eliminate crop colonization. The emergence of SE strains resistant to multiple antibiotics presents the need for alternative treatments and the results of these experiments show that an OAM may be a cost efficient and effective tool however the method of application of the OAM may alter effectiveness.